Smart Aquarium System Dilengkapi Rekomendasi Perawatan Spesifik Berdasarkan Jenis Ikan Hias - Masril, Mardhiah; Ikhwan Nursyam; Yogi Wiyandra (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2026)
Keeping ornamental fish in an Aquarium requires intensive care, particularly in maintaining a consistent feeding schedule and water quality. Negligence in maintenance can adversely affect the Aquarium ecosystem and fish health. Beyond cleanliness, the utilization of technology to create a more natural environment for the fish and a relaxing effect for the owners is still rarely developed. This research aims to design and build a microcontroller-based Smart Aquarium System as an efficient and interactive solution for automated fish care. This automation and educational medium is expected to assist user in managing Aquariums without the need for continuous manual intervention. The System is designed to perform automatic feeding schedules, water purification through a filtration System, and is equipped with a relaxation music player feature to create a more conducive atmosphere. This study employs the Research and Development (R&D) method, which includes the stages of problem identification, data collection, System design, implementation, testing, and evaluation. The System is built using an Arduino microcontroller as the central controller, integrating components such as temperature/water quality sensors, a servo motor for the automatic feeder, a water pump for filtration, and an audio module for the music feature. The test results show that the device functions as designed, where the System is capable of delivering feed precisely according to the determined schedule and maintaining optimal water circulation. The implementation of this Smart Aquarium has proven effective in increasing the efficiency of ornamental fish maintenance and providing added value in the form of convenience through integrated automation features